Spectrophotometry in Infrared Region: A New, Low Cost and Green Way to Analyze Tablets of Rifaximin - Kogawa, Ana C.; Nunes Salgado, Herida Regina (Current Pharmaceutical Analysis, 2018)
Background: Rifaximin is an oral antimicrobial, which, until now, does not have standardized analytical methods in most official compendia. The literature shows few methods for the detection of drug, but has no analytical method for the determination of rifaximin in the pharmaceutical product. The lack of environmentally friendly methods with the use and minimal generation of toxic waste is also a gap. Methods: This work proposed the development and validation of an infrared spectrophotometry method for the determination of rifaximin in tablets. Results: The method was linear over the concentration range of 1.0-3.5 mg with correlation coefficient 0.9997 and the limits of detection and quantification of 0.20 and 0.61 mg, respectively. Conclusion: The validated method was adequate, reliable, fast, economical and eco-friendly for the routine quality control of rifaximin in tablets. In the current fight against climate change, we can and must do our role , even if the role part is to develop and validate environmentally friendly method for routine use in the quality control of drugs and medicines in laboratories and pharmaceutical industries.
Keywords: method validation